Caracterización de la fibra del pseudotallo del plátano como potencial refuerzo para la elaboración de materiales compuestos (2023)
In this work, the pseudostem fiber of the banana variety Hartón (Musa paradisiaca) from agricultural residues of the department of Córdoba was characterized in order to evaluate its potential as a reinforcement of polymeric matrix composite materials. The fibers were extracted through the debarking process and dried at temperatures of 40° and 90°C. Morphological characteristics were determined by scanning electron microscopy SEM and stereoscopy. Fourier transform infrared tests - FTIR, bromatology and thermogravimetry - TGA allowed the chemical characterization; the mechanical properties were obtained by tensile tests. A statistical analysis was carried out that allowed to relate the diameters with the mechanical properties and drying temperatures. Microfibrils composed of cellulose, arranged helically within the fiber and agglutinated mainly by lignin and hemicellulose, were observed. FTIR analysis corroborated these components, as well as functional groups such as hydroxyl and aromatic. The bromatological tests showed that the fiber has 13.63% lignin, 41.17% cellulose and 11.51% hemicellulose. Experimental values of Young's modulus, maximum tensile strength and deformation were obtained for fibers dried at 40°C of 13.6±5.7 GPa, 236.4±112.9 MPa and 1.6±0.3%, respectively. While for the fibers treated at 90°C, 12.3±4.5 GPa, 227.0±97.0 MPa and 1.6±0.3, respectively were obtained. It was concluded that, on average, the drying condition did not significantly affect the diameter of the fibers or their mechanical properties. On the other hand, at smaller diameters higher mechanical properties will be obtained. In the fibers dried at higher temperatures, greater surface degradation is evident